2019
DOI: 10.1021/acs.jafc.8b07068
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Ring Methyl Groups in 2′,3′-Benzoabscisic Acid Analogues

Abstract: Five analogues of iso-PhABA (20) developed earlier by our research group were designed and synthesized. The bioassay results show that the number and position of methyl groups along with the substitution of hydrogen atoms of the methyl group have a great influence on the activity. Compared with iso-PhABA, the inhibitory activity of diMe-PhABA (21) on seed germination and rice seedling growth decreased slightly; however, it significantly reduced the capability of inhibiting wheat embryo germination. Both 3′-deM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…thaliana Stomatal Closure Assay. 28 A. thaliana seeds were sterilized with 70% ethanol for 10 min, then they were rinsed with double distilled water for 6−7 times, and the excess water was sucked away. These seeds were dibbled in a petri dish of 1/2 MS solid culture medium, dried, sealed by a split film, and placed in a refrigerator at 4 °C for vernalization for 3 days, and the petri dish is transferred to an incubator for cultivation for 5 days under the conditions of 25 °C, 16 h of illumination, and 22 °C and 8 h of darkness.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…thaliana Stomatal Closure Assay. 28 A. thaliana seeds were sterilized with 70% ethanol for 10 min, then they were rinsed with double distilled water for 6−7 times, and the excess water was sucked away. These seeds were dibbled in a petri dish of 1/2 MS solid culture medium, dried, sealed by a split film, and placed in a refrigerator at 4 °C for vernalization for 3 days, and the petri dish is transferred to an incubator for cultivation for 5 days under the conditions of 25 °C, 16 h of illumination, and 22 °C and 8 h of darkness.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In 2019, Wan et al, designed and synthesized five analogues of an earlier 2′,3′-iso-PhABA (Wan et al, 2019). Bioassay results showed that the number and position of methyl groups and the substitution of hydrogen atoms on methyl groups have great influence on the activity.…”
Section: Figurementioning
confidence: 99%
“…2). 15,[17][18][19][20][21][22] In the initial literature report describing the synthesis of the tetralone ABA 5, the (+)-enantiomer was found to have higher activity than ABA in both a corn cell growth inhibition assay as well as a seed germination inhibition assay in Arabidopsis. 15 Han et al reported that the racemic tetralone ABA (±)-5 had higher activity than racemic ABA ((±)-1) in seed germination assays in Arabidopsis, lettuce and in a rice seedling growth inhibition assay.…”
Section: Introductionmentioning
confidence: 99%